Optimization and control of a stand-alone hybrid solid oxide fuel cells/gas turbine system coupled with dry reforming of methane. (June 2017) - Wu, Wei; Chen, Shin-An; Hwang, Jenn-Jiang; Hsu, Fu-Teng
Highlights: The new stand-alone hybrid SOFC/GT power system and its control application is presented. The initial operating conditions are determined by solving a constrained optimization algorithm. The new plantwide control configuration is developed in Aspen Dynamic ® environment. The plantwide control configuration is composed of the inventory control, the air/fuel cross-limiting combustion control and the IMC-based multicontrol loops. Abstract: This paper presents the hybrid solid oxide fuel cells (SOFC)/gas turbine (GT) system coupled with dry reforming of methane (DRM). The DRM is a syngas producer by consuming greenhouse gas. The stand-alone (off-the-grid) power system is developed by using a combination of a post-burner, recuperators and pressurized recycles in place of external energy supplies. To address the stand-alone operation and meet the complete combustion condition for the burner, the optimal operating conditions are initially determined by solving a constrained optimization algorithm for maximizing the hybrid power efficiency, and the dynamic control loops are implemented in a plantwide environment. In the proposed plantwide control strategy, the inventory control framework is added to regulate the plant component inventory, an air/fuel cross-limiting combustion control is added to ensure complete combustion and reduce heat loss, and the power and CO2 emission control configuration is added to achieve the quality control performance. Finally, the simulation shows that the IMC-based multi-loop control scheme can efficiently regulate the total system power and control CO2 emissions per kWh of electricity as well.